EMOTIONAL INTELLIGENCE IN EDUCATION: GLOBAL RESEARCH TREND - Mohamed Adnan, Nor Syamimi; Suryani, Ina; Sulaiman, Suzana; Johari, Noor Farahhein; Sabri, Masturah; Abd Halim, Jasin (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Emotional intelligence (EI) has become an increasingly important area of study in the field of education, recognized for its role in shaping student achievement, psychological well-being, and social development. However, despite its growing prominence, research on EI in education remains scattered across disciplines, making it difficult to capture global patterns and thematic directions. To address this gap, this study conducts a comprehensive bibliometric analysis to map the research trends, collaborative networks, and thematic hotspots of EI in educational contexts. Data were collected from the Scopus database through an advanced search using the keywords emotional, intelligence, education, and psychological, limited to English-language publications. A total of 553 documents were retrieved, cleaned, and harmonized using OpenRefine. Descriptive statistics and trend graphs were generated using the Scopus Analyzer, while VOSviewer software was employed to construct visualization maps for co-authorship, co-citation, and keyword co-occurrence. The analysis reveals a consistent upward trend in publications from 2004 to 2024, with China, the United States, the United Kingdom, and Malaysia emerging as leading contributors, while Spain recorded the highest citation impact with 1,854 citations. Co-authorship analysis identified 34 countries surpassing the minimum threshold, resulting in eight clusters of international collaboration, with China and the United Kingdom positioned as central hubs of partnership. Keyword mapping highlighted dominant themes such as leadership, higher education, academic performance, and psychological well-being, demonstrating the multidimensional scope of EI research in education. These findings contribute to the body of knowledge by offering a comprehensive overview of the global intellectual structure, guiding future research directions, and underscoring the potential of EI as a vital framework for advancing educational practice and policy worldwide.